2020
DOI: 10.1038/s41598-020-74815-1
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of emergency ophthalmology services in Taiwan: a nationwide population study

Abstract: The aim of this study was to conduct a nationwide survey of the use of emergency ophthalmology services using a sub-dataset of one million beneficiaries sampled from Taiwan’s National Health Insurance Research Database (NHIRD) for the years 2008 through 2012. By analyzing this population dataset, the study illustrates the disease landscape of emergency eye care services. The five-year, one-million-person NHIRD sub-dataset for 2008 through 2012 was used to explore emergency visits and ophthalmology specialty vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
5
0
Order By: Relevance
“… 40 Furthermore, a nationwide survey conducted in Taiwan regarding the use of emergency ophthalmology services between 2008 and 2012 reported a percentage of urgent visits of 48.2%. 41 Considering the situation during the pandemic in Italy, Babu et al. 32 and Pellegrini et al 34 and reported that respectively 60% and 57.3% of cases presenting during the lockdown were unlikely to be emergency cases.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Furthermore, a nationwide survey conducted in Taiwan regarding the use of emergency ophthalmology services between 2008 and 2012 reported a percentage of urgent visits of 48.2%. 41 Considering the situation during the pandemic in Italy, Babu et al. 32 and Pellegrini et al 34 and reported that respectively 60% and 57.3% of cases presenting during the lockdown were unlikely to be emergency cases.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple logistic regression analysis, we selected explanatory variables based on previous studies that have reported possible factors that may affect ophthalmology utilization. These variables included age, 29 sex, 29,30 marital status, 31 ethnicity, 23 educational level, personal income, 23 and health insurance status. 23,30 To determine whether ophthalmic visits and vision examinations were affected by eye conditions other than glaucoma, we included several other eye conditions in the analysis.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…This research attempted to probe and compare the difference between the landscape of admitted patients in those countries and Taiwan based on the Taiwanese National Health Insurance Research Database (NHIRD). Additionally, with our previous studies that examined outpatient and emergent eye care services of Taiwan [ 5 , 6 ], we hope to complete the overall panorama of ophthalmology service in Taiwan. Hopefully, these insights might help guide policy decisions to improve resource allocation and enable better understanding of ophthalmic epidemiology.…”
Section: Introductionmentioning
confidence: 99%